Beneficial Assessment for Meaningful Learning in CLIL - Ortiz-Castro, Patricia (My University, 2017)
Globalisation is changing the world of education. This worldwide movement has originated the development of CLIL approach in many countries to improve the learning of the additional language and content in this language. CLIL is a relatively new and an innovative approach, for this reason, there is a lack on teachers’ training, materials on Assessment tools. It is fundamental that this situation changes because, as this study shows, Assessment has a really important impact on pupils’ motivation and self-esteem; two of the main factors that have an influence on the achievement of the meaningful learning. This Master’s Dissertation tries to give information and foundations of meaningful learning in CLIL context through Assessment, analysing four ways of assessing in CLIL to describe the beneficial aspects for the meaningful learning in this approach trough the Assessment. Four methods of Assessment were explored in 6th Grade on Primary education in a bilingual school where they are carried out in real situations. Teachers and students could express their opinions through interviews and surveys that also gave information about their emotional and motivational factors in learning for meaning attribution. These data were analysed and compared with data from the literature review documents. Findings show that there is not only one beneficial Assessment tool, but that the Assessment has to have some characteristics in order to be beneficial for students’ meaningful learning. Teachers should assess students following these characteristics, that are described in the discussion section of this document, in order to promote a beneficial self-esteem pattern in learning and intrinsic motivation. In this way, pupils will avoid only memorization and they will make the learning useful in their real life.
Keywords: CLIL approach; assessment; meaning attribution; pattern of self-esteem and motivation; educación bilingüe; Máster Universitario en Educación Bilingüe